University Students' Perception Towards Webtoon Application for Their English Reading Habit - Zalfara Tiar Khoirunisa; Flora; Riyantika, Fajar (English Language Education Study Program, 2024)
People nowdays tend to find information and entertaiment through a reading medium, which is currently widely available in digital form. Webtoon is a comic application in digital form that is widely used today. Webtoon presents various comic genres that can be accessed easily. There are many students use this Webtoon Application in reading English text. Therefore, knowing their perception of Webtoon in English reading activities are very important. In this context, perception is a thought. Based on the students' experience while using the Webtoon Application , whether they feel a lot of improvement or vice versa. This research aims to investigate the perceptions university students regarding the use of Webtoon Application for their English reading habit. The participants of this research were English speakers education students from various universities in Indonesia who read various comics in English through Webtoon Application. The method used in this research is descriptive-quantitative with data collection techniques using close-ended questionnaires and open-ended interviews. In this research, it was found that students have positive perceptions towards Webtoon Applications. Because it was simple to access. Webtoons can improve vocabulary, understanding of grammar, the use of idioms, and understanding the content and ideas in narrative texts.